Actinomadura vinacea isolated from a nonhealing cutaneous wound in a cat. (15th October 2018) - Wells, Bridgette; Burnum, Anne L.; Armstrong, Juliet; Sanchez, Susan; Stanton, James B.; Camus, Melinda S.
Abstract: A 6‐year‐old, spayed female, domestic shorthair cat was presented to the University of Georgia Veterinary Teaching Hospital for a 3‐year history of a nonhealing wound on the right tarsus. The wound temporarily resolved with medical management, but intermittently recurred when antimicrobials were discontinued. At presentation, the wound had become refractory to antimicrobial therapy. Physical examination revealed a 1 cm diameter crust along the medial aspect of the right tarsus. Proximal to the crust, were 2 non‐painful, fluctuant swollen areas that were free of drainage. Cytologic evaluation revealed atypical granulated cells, and a mesenchymal neoplasm was interpreted as a top differential diagnosis. Histopathology revealed marked, chronic, multifocal, pyogranulomatous dermatitis with abundant intralesional colonies of gram‐positive, acid‐fast‐negative, filamentous bacteria. PCR and sequencing confirmed the infection to be caused by Actinomadura vinacea .